Simplified Method for the Power Flow and Transmission Efficiency Analysis of Epicyclic Gear Train - Xue Huiling; Liu Geng; Yang Xiaohui (Jixie chuandong)
Based on virtual power theory,the power flow and efficiency analysis of differential gear train and closed planetary gear train are accomplished. Firstly,the gear train power flow and virtual power flow diagrams are established with or without considering the gear meshing power loss,the flow of power and virtual power is analyzed. Then,the gear meshing power loss and gear train transmission efficiency are calculated,the expression of gear train transmission efficiency is obtained. Finally,the influence of related design and manufacturing parameters on the efficiency of the gear train is analyzed and discussed. The results show that reasonable transmission type,number of teeth,speed ratio and gear manufacturing grade can efficiently increase gear train transmission efficiency. The proposed method is simple and can be used for the design of gear train.